Respuesta :
x—2 equations combined:
2(2x - 3y) + 3(5x + 2y) = 2(11) + 3(18)
4x - 6y + 15x + 6y = 22 + 54
19x = 76
x = 4
y—1st equation, substitute x:
2(4) - 3y = 11
8 - 3y = 11
3y = - 3
y = - 1
Answer: x = 4, y = - 1
Proof—2nd equation:
5(4) + 2(- 1) = 18
20 - 2 = 18
18 = 18
2*2x-2*3y=2*11-------------------------(1)
3*5x+3*2y=3*18------------------------(2)
add equation(1)&equation(2)
_____________________________
4x+15x=22+54
19x=76
x=4
put the value of x in equation(1)
2*2*4-2*3y=2*11
16-6y=22
16-22=6y
6y=-6
y=-1
x=4
3*5x+3*2y=3*18------------------------(2)
add equation(1)&equation(2)
_____________________________
4x+15x=22+54
19x=76
x=4
put the value of x in equation(1)
2*2*4-2*3y=2*11
16-6y=22
16-22=6y
6y=-6
y=-1
x=4